Pencegahan Penurunan Kognitif pada Lansia melalui Finger Game - Ratna Kusuma; Tatik Trisnowati (Politeknik Piksi Ganesha Indonesia, 2026)
Finger games are an alternative activity for the elderly to prevent cognitive decline. Cognitive function is a person's ability to recognize and interpret things in the environment. Cognitive function is closely related to the human brain. The brain functions as a visual perception as well as the ability to calculate, speak, and process all information and memory. In some elderly who have entered the aging phase, symptoms of cognitive dysfunction include decreased concentration, difficulty memorizing information, greater forgetfulness, and difficulty describing certain forms or functions. The purpose of this health education activity is to demonstrate finger games as an alternative to prevent cognitive decline in the elderly. Participants in this activity were 12 elderly at the ILP Seruni-Setabelan Surakarta, which is one of the Posyandu supported by the Community Health Center Setabelan in Surakarta. The examination results showed that the average cognitive function score of respondents before the finger game intervention (pre- intervention) was 20.5, while after the finger game intervention (post- intervention) it increased to 25.6. There was a difference of 5.1 points in increase, indicating an increase in cognitive function in the elderly after the finger game intervention. And the elderly are able to redemonstrate finger games independently.